The Learning Management of 7-Step Inquiry Learning together with Collaborative Learning to Enhance Learning Achievement and Collaborative Learning Skills in Science of Secondary 3 (Grade 9) Students - Watcharaporn Niawbubpha, Saiphin Siharak (International Journal of Advanced Science and Technology, 2020)
The purposes of this research were: 1) to compare learning achievement in science of secondary 3 (grade 9) students between before and after learning by using 7-step inquiry learning together with collaborative learning, and 2) to compare collaborative learning skills in science of secondary 3 (grade 9) students between before and after learning by using 7-step inquiry learning together with collaborative learning, The samples used in the research were 20 secondary 3 (grade 9) students in Suraoklong 19 School, Chachoengsao Province, the second semester of the academic year 2019.  The research instruments were:  1) Learning Management Plan. 2) Learning Achievement in Science Test and 3) Collaborative Learning Skills in Science Test, which created by the researcher. The statistics used in the data analysis were average, standard deviation and dependent samples t-test. The results of the study revealed that: 1) learning achievement in science of secondary 3 (grade 9) students  who learning by using 7-step inquiry learning together with collaborative learning after studying higher than before studying at the statistically significant.05 level, and 2) the collaborative learning skills of secondary 3 (grade 9) students who learning by using 7-step inquiry learning together with collaborative learning after studying higher than before studying at the statistical significance level of .05